Accuracy, predictability and prognostic implications of fine‐needle aspiration biopsy for parotid gland tumours: A retrospective case series. (31st May 2021) - Boldes, Tomer; Hilly, Ohad; Alkan, Uri; Shkedy, Yotam; Morgenstern, Sara; Shpitzer, Thomas; Bachar, Gideon; Mizrachi, Aviram
Abstract: Objective: To evaluate the precision and utility of fine‐needle aspiration (FNA) in differentiating between benign and malignant parotid tumours, and the implications of FNA results on management and outcomes. Design: Retrospective case series. Setting: Tertiary medical centre. Participants: All adults who underwent preoperative FNA, followed by postoperative histological examination, between 1986 and 2014. Main outcome measures: Differences in clinical management and outcomes of patients with parotid masses in light of FNA results. Results: We analysed 505 samples from 485 patients. According to histopathological results, preoperative FNA successfully identified benign tumours in 89% of the cases (362/405) and only 59% of malignant tumours (59/100). Overall sensitivity and specificity of FNA in distinguishing between different subtypes of benign lesions were 80% and 99%, respectively, whereas positive predictive value (PPV) and negative predictive value (NPV) were 85% and 98%. Moreover, malignant lesions subtyping had high false‐positive and false‐negative rates with sensitivity, specificity, PPV and NPV of 44%, 100%, 75% and 99%, respectively. Additionally, when FNA falsely classified malignant tumours as benign, surgeries were inappropriately delayed and the durations of surgeries and hospitalisations were shorter, compared to true malignant FNA results. Interestingly, survival was not affected in falsely benign lesions that were mostly low‐grade, conversely non‐diagnostic FNA for malignant tumours resulted in decreased survival. Conclusions: Our findings highlight the limitations of FNA as a decision‐making tool in preoperative evaluation of parotid masses. Clinicians should take into account that FNA is inaccurate for identifying specific subtypes of malignant lesions, which may eventually delay treatment and influence outcome.